NEPOTISME DALAM PERSPEKTIF HADIS: Suatu Kajian Hadis Mauwdû’î - Sabir, Muhammad (Hunafa: Jurnal Studia Islamika, 2010)
This article deals with nepotism in the hadîth perpective. Based on the takhrîj al-ahâdîth related to nepotism, their sub-theme, their number of mukharrij and their number of hadîth  can be classified in detail as follows: the ahâdîth on nepotism in Shahîh al-Bukhârî  are 3 mutûn al-hadîth; in Shahîh Muslim are 2 mutûn al-hadîth; in Sunan al-Turmûdhî  is 1 matn hadîth; in Sunan al-Nasâ’î is 1 matn hadîth; in Musnad Ahmad are 2 mutûn al-hadîth and in Mustadrak al-Hâkim are 2 mutûn al-hadîth. Based on these findings, the number of hadîth  on nepotism are 11 mutûn al-hadîth and those ahâdîth are found in the six-hadîth references. However, of all the ahâdîth found, none of them permitted to commit nepotism.Kata Kunci: nepotisme, takhrij hadis, syarah hadis